2021
DOI: 10.1002/alz.12401
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a multi‐site randomized controlled trial of aerobic exercise for older adults with amnestic mild cognitive impairment: The EXERT trial

Abstract: Introduction:Effective strategies to recruit older adults with mild cognitive impairment (MCI) into nonpharmacological intervention trials are lacking.Methods: Recruitment for EXERT, a multisite randomized controlled 18-month trial examining the effects of aerobic exercise on cognitive trajectory in adults with amnestic MCI, involved a diverse portfolio of strategies to enroll 296 participants.Results: Recruitment occurred September 2016 through March 2020 and was initially slow. After mass mailings of 490,323… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…While mass mailings have been used for recruitment into AD prevention trials and brain health registries, our findings suggest that mass mailings may be ineffective for recruitment into pharmacologic trials of mild to moderate AD 13–16 . Mass mailings accounted for more than half of participants randomized into EXERT, whereas 25% were recruited from existing lists of eligible patients from participating sites 11 . This underscores the need to publish AD trial recruitment metrics to inform the evidence base around best practices for recruitment.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…While mass mailings have been used for recruitment into AD prevention trials and brain health registries, our findings suggest that mass mailings may be ineffective for recruitment into pharmacologic trials of mild to moderate AD 13–16 . Mass mailings accounted for more than half of participants randomized into EXERT, whereas 25% were recruited from existing lists of eligible patients from participating sites 11 . This underscores the need to publish AD trial recruitment metrics to inform the evidence base around best practices for recruitment.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to EXERT, we found that major reasons for screen failure in T2 Protect AD were similar across racial and ethnic groups. 11 Thus, enrollment of underrepresented populations into future AD clinical trials will require concerted and targeted recruitment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital tools (eg emails, social media advertisements) are effective for recruiting older participants 66 even those with mild cognitive impairment. 67 However, it is indispensable to take into account limitations, barriers and needs of the target population to better adapt devices and interventions. 68 , 69 One of the main barriers to older people using mobile technology and devices should be as simple as possible and if applicable, easy to wear.…”
Section: Discussionmentioning
confidence: 99%
“…As a teaching tool, infographics enhance engagement, memory retention, recall, comprehension, and development of communication skills. 7 8 In the current climate of the coronavirus pandemic, infographics have been increasingly employed for patient education. For example, infographics were used to promote the goal of “flattening the curve” by encouraging hygienic practices such as handwashing and appropriate mask-wearing and providing information on local public health guidelines.…”
Section: Identifying the Infographic’s Objectivesmentioning
confidence: 99%